An Approach Towards Designing Relational Database With Transaction Operations - Kumar, Kunal; Kumar Azad, Sachindra (International Journal of Computer Sciences and Engineering, 2025)
A transaction processing on relational database perform as single logical unit of work, which either executed completely or not at all on database system. A transaction processing on database perform mainly two basic operations read and write operation on the database system. Read operations fetch the content of the database using some standard SQL query and retrieve the data from database to the local logical buffer in main memory. In other hand, write operations, update of the local logical buffer and send back the data from the local main memory to database system for permanent storage. In this paper, we are going to know various applications of transactions schedules and how to resolve the various issues that implicitly generated during the transaction schedule generation. Every transaction has many operations on it; all these operations may or may not be of same duration.